Single pulse all-optical toggle switching of magnetization without gadolinium in the ferrimagnet Mn2RuxGa - C. Banerjee (Nature Portfolio, 2020)
Femtosecond laser pulses allow for extremely fast switching of magnetization in ferromagnetic films, but all examples so far contained gadolinium. Here the authors demonstrate room temperature all-optical toggle switching in a ferrimagnetic manganese-based half-metal without gadolinium.